Faecal excretion of total and acid extractable phosphorus in dairy cows fed rations with different levels of phosphorus. (19th May 2015) - Nordqvist, Maria; Spörndly, Rolf; Holtenius, Kjell
Abstract: BACKGROUND: The phosphorus (P) originating from livestock operations causes eutrophication. Determination of acid extractable P (AEP) in cattle faeces has been proposed as a tool to identify excessive P feeding. The method has not yet been evaluated in controlled studies with cows subjected to individual recording of P intake. Thus the present study focused on investigating the relationship between different P fractions in faeces from cows fed rations with varying P content. The study also investigated whether AEP in faeces could be used to estimate dietary P intake in relation to the P requirement. RESULTS: The results showed that acid extractable P predicted P overfeeding. P fed in excess of requirements was largely excreted as acid extractable P. The unavailable and/or inevitably lost P fractions in the diets were smaller than assumed. CONCLUSION: This study demonstrates in experimental studies a positive relationship between measured AEP and indirectly calculated regulated P. Any P fed in excess of requirements was largely excreted as AEP. This fraction is thought to be the most mobile P fraction with regard to potential runoff losses. However, the unavailable and/or inevitably lost P fractions in the diets were smaller than assumed. © 2015 Society of Chemical Industry